Model analisis tahap kawasan sensitif alam sekitar di negeri Johor (a model of level of environmental sensitive areas in Johor) - Asmawi, M. Zainora (2018)
This work highlights an analysis model concerning the level of environmental sensitive areas (ESA) in Johor, which could be classified into three levels. This exercise formulated a more detailed criteria following numerous sectoral ESAs. Each of the criteria holds its specific condition which they are then turned into a weightage matrix and spatial GIS mapping. These products are dedicated for the state of Johor, indicating the level of ESAs of the its natural resources.